Research Notes: Industry Differences in Environmental Uncertainty and Organizational Characteristics Related to Uncertainty - Hrebiniak, Larence G.; Snow, Charles C. (Academy of Management Journal, 1980)
The article discusses the relationship between organizations and the environment. The study examines whether or not industry type is an important variable in the type of uncertainty felt by executives in an organization. Also discussed are the types of organizational characteristics associated with uncertainty, including influence patterns and organizational structure. According to the author, the type of industry plays a role in determining characteristics such as environmental uncertainty, structural decentralization and intraorganizational influence.